Development of Self‐Doped Conjugated Polyelectrolytes with Controlled Work Functions and Application to Hole Transport Layer Materials for High‐Performance Organic Solar Cells. Issue 12 (7th March 2016) - Jo, Jea Woong; Jung, Jae Woong; Bae, Seunghwan; Ko, Min Jae; Kim, Heesuk; Jo, Won Ho; Jen, Alex K.‐Y.; Son, Hae Jung
Abstract : A series of anionic self‐doped conjugated polyelectrolytes (CPEs) by copolymerization of a 1, 4‐bis(4‐sulfonatobutoxy)benzene moiety with different counter monomers of thiophene, bithiophene, and terthiophene is reported. The CPEs show high conductivity of ≈10 −4 S cm −1 due to being self‐doped in a neutral state and exhibit excellent hole transporting property in the out‐of‐plane direction, compared with poly(3, 4‐ethylenedioxythiophene):poly(styrene‐sulfonate) (PEDOT:PSS). Moreover, the CPE incorporating a less electron‐donating unit from terthiophene to thiophene exhibits a higher work function and therefore, PhNa‐1T incorporating thiophene shows a relatively high work function of 5.21 eV than 4.97 eV of PEDOT:PSS. This can induce a higher internal field in the solar cell device, facilitating efficient charge collection to the electrode. As a result, polymer solar cell devices incorporating the CPEs as a hole transporting layer achieve enhanced photovoltaic performances from those of the conventional PEDOT:PSS‐based devices. The solar cell efficiency reaches up to 9.89%, which is among the highest values demonstrated by PCE‐10‐based normal‐type organic solar cells. Abstract : A series of anionic self‐doped conjugated polyelectrolytes is synthesized by copolymerizing dibromo‐1, 4‐ bis (4‐sulfonatobutoxy)benzene with borate compounds of thiophene, bithiophene, and terthiophene (ThCPEs). Organic solar cells using ThCPEs as the hole‐transporting layer show higher photovoltaic performances than the device derived from poly(3, 4‐ethylenedioxythiophene):poly(styrene‐sulfonate) (PEDOT:PSS) because the ThCPEs exhibit better hole‐transporting properties in the out‐of‐plane direction and higher work functions than PEDOT:PSS.